Living with yourself according to Emily Dickinson - La Mattina, Daniela (Dialogoi. Rivista di studi comparatistici, 2020)
Emily Dickinson’s original poems and style profoundly influenced the 20th-century poetry with her short lines and verses about her inner life, thoughts and feelings. To this day She is a distinctive voice in the American literature and in the World Wide Web because followed by several teenagers who uses her quotations in their profiles of social media overall in this emergency universal lockdown. In Emily ‘s poetry we can find in fact a sort of relief and the solutions to our drama of loneliness and imprisonment already lived by the poet who conveys us the right attitude towards isolation that can be also joy, self- consciousness and happiness.